PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP OPINI GOING CONCERN - Fatimah Febriyanti Purnamasari; Reni Oktavia; Chara Pratami Tidespania Tubarad (Jurnal Akuntansi dan Keuangan (JAK), 2020)
The purpose of this study was to examine the effect of good corporate governance on going concern opinion. Indicators used to measure good corporate governance is institutional ownership, managerial ownership, and the proportion of the independent board of commissioners. Meanwhile, going concern opinion as the dependent variable is measured by a dummy variable. This study uses secondary data with a population of companies listed on the Indonesia Stock Exchange (BEI) 2014-2018. The method used to determine the sample using purposive sampling. Consisting of 50 industrial manufacturing companies with 250 samples outlier to 243 samples. The analysis method used is logistic regression. The results of hypothesis testing show that managerial ownership has a positive effect on going-concern opinion. Meanwhile, institutional ownership and the proportion of independent commissioners do not have a significant effect on going-concern opinion.